Immune Neuroendocrine Interactions during a Fungal Infection in Immunocompetent or Immunosuppressed Hosts - Rodriguez Galan, Maria Cecilia (2010)
The yeast Candida albicans belongs to the microflora of healthy individuals, although it can infect a variety of tissues ensuing changes in the host's immune status. To evaluate the effect of neuroendocrine input on the early immune response during the fungal infection, we use a 3-day paradigm of chronic varied stress in Wistar rats infected with C. albicans. We find that stress mediators contribute to the spread of the fungus and downregulate critical functions of phagocytic cells at the infection site. Phenotypic and functional alterations of effector cells account for the decreased resistance to candidiasis and condition the development of the adaptive response. Stressed hosts exhibit a higher fungal burden in kidneys and livers associated with hyphal forms. The hepatic inflammatory reaction is compromised with severe steatosis, increment of functional enzymes, marked lipid peroxidation and hepatocyte apoptosis. Moreover, infection-related sickness symptoms are significantly increased by exposure to stress with anorexia, weight loss, lack of leptin and depletion of glycogen depots. Food deprivation exacerbates the liver injury. Stress mediators perturb the complex immune and metabolic program that operates early during fungal spread and promotes severe tissue damage